2016
DOI: 10.3390/magnetochemistry2010007
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Magnetic Properties of the Spin Crossover Linear Trinuclear Complex [Fe3(furtrz)6(ptol)2(MeOH)4]·4(ptol)·4(MeOH) (furtrz: furanylidene-4H-1,2,4-triazol-4-amine ptol: p-tolylsulfonate)

Abstract: Abstract:The furan-functionalised 1,2,4-triazole ligand furanylidene-4H-1,2,4-triazol-4-amine (furtrz) has been incorporated into the trinuclear complex Fe 3 (furtrz) 6 (ptol) 2 (MeOH) 4 ]¨4(ptol)¨4(MeOH) (ptol = p-tolylsulfonate) composed of µ 1,2 -triazole bridges between iron(II) sites, as per one-dimensional chain materials, and terminally coordinated ptol anions and methanol molecules. Magnetic susceptibility measurements reveal a gradual single-step spin crossover (SCO) behavior of one third of the iron(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
(28 reference statements)
2
13
0
Order By: Relevance
“…A further study can be followed by synthesis of similar compounds with different degree of aromatic substitutions, either from the triazole ligands or from the counter anions. Furthermore, the relatively low transition temperature (120 K) for this compound is consistent with other similar discrete molecular species containing bulky aromatic 1,2,4-triazole ligands [19,[24][25][26].…”
Section: Magnetic Susceptibility and Mössbauer Spectroscopysupporting
confidence: 83%
See 2 more Smart Citations
“…A further study can be followed by synthesis of similar compounds with different degree of aromatic substitutions, either from the triazole ligands or from the counter anions. Furthermore, the relatively low transition temperature (120 K) for this compound is consistent with other similar discrete molecular species containing bulky aromatic 1,2,4-triazole ligands [19,[24][25][26].…”
Section: Magnetic Susceptibility and Mössbauer Spectroscopysupporting
confidence: 83%
“…The multiple intra-and inter-molecular H-bonding interactions found in the crystal lattice explain the strong cooperativity between the active Fe(II) centers. Interestingly, even though studies have shown that ligands with bulky aromatic substituents and aromatic anions might have a "dilute or separation effect" on the overall cooperativity of the SCO compounds [19,26]. The abrupt transition observed here stands for an example with the supramolecular interactions overcome the "aromatic dilute effect".…”
Section: Magnetic Susceptibility and Mössbauer Spectroscopymentioning
confidence: 69%
See 1 more Smart Citation
“…The phenomenon of SCO was discovered almost one hundred years ago [3,4] and refers to the change of the ground spin state of transition metal ions with the electronic configuration d 4 − d 7 from the low-spin (ls) state to the high spin (hs) one under action of temperature, light or external pressure (see review papers [1,[5][6][7]). Last years, many works were devoted to binuclear [8][9][10][11], trinuclear [12][13][14] and tetranuclear [15][16][17][18][19] iron(II) SCO systems. SCO can take place if the molecular unit of a crystal cell has at least one ion with the electronic configuration d 4 − d 7 and closely spaced low-spin (ls) and high-spin (hs) levels of this ion.…”
Section: Introductionmentioning
confidence: 99%
“…A novel Fe(II) mononuclear species made with a pyridylmethyleneaniline ligand featuring an isopropyl group exhibits hysteresis resulting from the coupling of the SCO transition with a process of conformational isomerism of the latter substituent [11]. In addition to mononuclear systems, this issue channels the presentation of a novel trinuclear spin transition complex [12]. …”
mentioning
confidence: 99%